2005
DOI: 10.1111/j.1751-1097.2005.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short‐ and Long‐term Ultraviolet B Irradiation on the Immune System of the Common Carp (Cyprinus carpio)

Abstract: Carp (Cyprinus carpio) were repeatedly exposed to 0, 60, 120 and 240 mJ/cm2 ultraviolet B (UVB) radiation three times in 1 week (short‐term exposure) or 12 times in 4 weeks (long‐term exposure). The effect of UVB on the functioning of the carp immune system was studied on day 2 after the final irradiation. After short‐term UVB exposure, the whole‐blood respiratory burst and cytotoxic activity were markedly enhanced, with parallel responses in both the number of circulating granulocytes and in the plasma cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 57 publications
(58 reference statements)
2
26
0
Order By: Relevance
“…In Experiment II, carp head kidney leucocytes were collected from the interface between densities 1.040 and 1.090 g ml ÿ1 , and for separation of rainbow trout head kidney leucocytes a one-step Percoll gradient (1.090 g ml ÿ1 ) was used. Cells were then washed twice, re-suspended into incubation or culture medium (RPMI-1640, supplemented with 3% Ultroser G, 0.5 mg ml ÿ1 sodium pyruvate, 2 mM L-glutamine, 100 IU ml ÿ1 penicillin, 100 mg ml ÿ1 streptomycin, and 10 mM HEPES, pH 7.4 [5]), and counted with trypan blue exclusion in a haemocytometer (viability >95%). The cell suspension was then adjusted to the desired concentration.…”
Section: Sampling Of Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…In Experiment II, carp head kidney leucocytes were collected from the interface between densities 1.040 and 1.090 g ml ÿ1 , and for separation of rainbow trout head kidney leucocytes a one-step Percoll gradient (1.090 g ml ÿ1 ) was used. Cells were then washed twice, re-suspended into incubation or culture medium (RPMI-1640, supplemented with 3% Ultroser G, 0.5 mg ml ÿ1 sodium pyruvate, 2 mM L-glutamine, 100 IU ml ÿ1 penicillin, 100 mg ml ÿ1 streptomycin, and 10 mM HEPES, pH 7.4 [5]), and counted with trypan blue exclusion in a haemocytometer (viability >95%). The cell suspension was then adjusted to the desired concentration.…”
Section: Sampling Of Fishmentioning
confidence: 99%
“…The concentration of IgM in carp plasma was measured by enzyme-linked immunosorbent assay (ELISA) [5]. Monoclonal mouse anti-roach IgM antibody (R1a4) was used as the trapping and detection agent after strong cross reactivity with carp IgM was established.…”
Section: Plasma Immunoglobulinmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental pollutants such as, e.g., polychlorinated biphenyls (PCBs) (Ouabius et al 2005) or municipal sewage effluent (Hoeger et al 2004) are immunotoxic and impair the ability of fish to respond to additional stressors (Köllner et al 2002). Prolonged changes in natural photoperiod (Leonardi and Klempau 2003), diet, temperature (Bly and Clem 1992;Le Morvan et al 1998), artificial or natural solar UV radiation (Markkula et al 2005a(Markkula et al , 2005bSalo et al 2000), and bacterial or viral diseases affect the immune system of teleost fish and Salmonidae in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Although the direct effects of exposure to UV radiation are likely minimal within the context of all the other environmental factors that cause very high levels of egg and larval mortality in marine organisms, studies have shown that UV-induced egg mortality could be as high as 32.5% for the planktonic copepod Calanus finmarchicus and considerably less (1.2%) for the Atlantic cod Gadus morhua in the waters of the estuary and Gulf of St. Lawrence, Canada (Browman et al, 2000). Other direct effects of UV exposure on fish eggs or larvae include malformation (Dong et al, 2007), retarded growth (Jokinen et al, 2008), lesion of skin, eyes, and brain (Blazer et al, 1997;McFadzen et al, 2000), and weakened immune system (Markkula et al, 2005, 2006). These pernicious effects may be higher for fish larvae that are often present in surface waters since UV-B (λ = 280-320 nm) exposure induces DNA damage in a variety of fish larvae such as Atlantic cod, northern anchovy Englausis mordax, icefish Cephalus aceratus and Japanese medaka Oryzias latipes (see Fukunishi et al, 2012 for references).…”
Section: Importance Of Light Radiation For Carotenoid Production and mentioning
confidence: 99%